Media and Conflict Reporting in Multicultural Nigeria - Abdulaziz Nasiru Muhammad (Lakhomi Journal Scientific Journal of Culture, 2025)
Nigeria’s multicultural landscape is both vibrant and prone to conflict. With over 250 ethnic groups and multiple religious traditions, the way the media report conflicts significantly influence public perception and social cohesion. This paper examines how Nigerian media report conflicts within diverse social contexts, focusing on reporting styles, ethical dilemmas, and their implications for peacebuilding. Through qualitative analysis of ethno-religious violence, misinformation on social media, and protest coverage, the study explores the strengths and weaknesses of conflict reporting in Nigeria. Grounded in Framing Theory and Peace Journalism Theory, the findings indicate that while some media outlets attempt to uphold professional and ethical standards, others unintentionally intensify social divisions through biased language and sensational reporting. The paper concludes with recommendations for conflict-sensitive journalism that promotes social harmony and strengthens democratic values in Nigeria.